Anti‐cancer therapy made easier: a 25‐year update. Issue 4 (22nd April 2021) - Davies, Amy; Lum, Caroline; Raju, Rachel; Ansell, Evan; Webber, Kate; Segelov, Eva
Abstract: In 1993, the Internal Medicine Journal published 'Chemotherapy made easier', outlining developments in supportive care of patients undergoing chemotherapy. This described the contemporary state of anti‐emetics, colony stimulating factors, cardiac toxicity, neurotoxicity, development of drug analogues and venous access devices. Twenty‐five years later, we update the measures that improve the tolerability of the plethora of new anti‐cancer therapies, which have extended well beyond traditional chemotherapy agents to include immunotherapy and targeted therapies. Optimisation of supportive care is paramount to allow safe delivery with the least possible impact on quality of life of these new treatments, many of which have resulted dramatically improved outcomes across multiple cancer types. This state of the art update summarises advances in supportive care therapies relating to improving the patient experience during and after anti‐cancer treatment, including new anti‐emetics, hair preservation techniques, bone marrow support and improved venous access devices; the ongoing challenge of neurotoxicity; and the advent of multidisciplinary sub‐specialised fields such as cardio‐oncology and oncofertility. Supportive care medications for immuno‐oncology therapies is a new section; these highly effective (although not universally so) agents were a mere illusion in 1993.